Effectivity of Cacao Rind Ethanol Extract in Inhibiting Streptococcus Pyogenes Growth In Vitro - Cynthia Dwi Ramadhanie; Sri Purwaningsih; Eko Budi Koendhori (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Infectious disease is still a common cause of illness and death in developing countries, such as Indonesia. One of the bacteria that causes infectious disease is Streptococcus pyogenes. Cacao fruit is a large commodity in Indonesia and has benefit for human. Cacao’s rind is known to contain several active compounds such as flavonoid and alkaloid that have antibacterial effect that can inhibit Streptococcus pyogenes growth. This research aims to evaluate the Minimum Bactericidal Concentration (MBC) of cacao rind ethanol extract in inhibiting Streptococcus pyogenes growth in vitro. Methods: This research was a laboratory experimental study, testing antibacterial activity of cacao’s rind ethanol extract in inhibiting growth of bacteria Streptococcus pyogenes using dilution method in vitro to know the MIC and MBC result. Sample of bacteria Streptococcus pyogenes was obtained from Balai Besar Laboratorium, Surabaya. Sample of cacao’s rind ethanol extract was extracted at Balai Materia Medica, Batu. Results: At the beginning this experiment was done to find the MIC and MBC of cacao’s rind ethanol extract against the growth of bacteria Streptococcus pyogenes, but the researcher can only find the MBC result, because the extract color is very dark, so the turbidity result of tubes P1 – P7 cannot be compared to control tube. From the results, the researcher draws a table showing how turbid and dark those tubes are. More (+) signs means more turbid or darker the tube is. From dilution test, the MBC of cacao’s rind ethanol extract against the growth of bacteria Streptococcus pyogenes is 12.5%. Conclusion: Cacao’s rind (Theobroma cacao L.) was quite effective in increasing the growth of bacteria Streptococcus pyogenes in vitro, the Minimum Bactericidal Concentration (MBC) is 12.5%